Svårklassryttares förberedelser för dressyrträning : för bäst lärande - Oscander, Anna (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2010)
SUMMARY There was no previous study in what high level dressage riders had for ideas of how to best prepare for their training sessions with an instructor. Neither any study of how high level dressage riders seemed to be more or less susceptible to the instructions from their instructor during their training sessions. If the sport had more knowledge about this, it might result in more riders on a higher level. The purpose of this study was to find out how high level dressage riders are preparing themselves for the best result for an instructor led training session and how they could bring as much as possible instructions from the coach. The two questions of the study were: How are high level dressage riders preparing themselves for a training session with an instructor, practically and mentally, and how can they affect their susceptibility to instructions? The study was carried out both by reviewing existing literature and studies in general education and pedagogy in the riding education, and by a qualitative interview study of six dressage riders who rode on a difficult level at the competitions, during the year of 2009. Five of the interviews conducted through a personal meeting, while the sixth interview was done by telephone. Three women and three men were interviewed. All interviews were recorded and then written out. It’s known that people have different ways of learning and dealing with new information. Our visual-, auditional- and kinetic senses are developed in different stages of our growth. Those are senses that we use more or less while learning something new. The riders often learned a lot by watching other good riders ride. One of the female riders really needed to go home and practice new exercises, to learn. Several riders felt that they had easy to understand verbal instructions and immediately follow and practice them. People need to fulfil some essential factors for living, before they can feel any need of development of themselves as persons. Those factors are: food, water and sleep, and after that comes security and then a need of a social network. After those three steps are fulfilled can they feel motivated to approve their own abilities as a person, such as technique training for a rider. Comparing this with the current study, stress caused by a lack of time, too much to do at work or no time to eat and sleep, affected the riders so they failed in focus and concentration during training. To re-focus, they often used short pauses. They were more often focused while training away from home. The conclusion of the study is that it’s important to organize and plan before a training, to feel calm and able to give all focus on the horse and the instructor when it’s time. Then they can learn as much as possible and that will increase the chances of fast development in the sport. The riders felt that they could increase their susceptibility to instructions on the training by: · Think about what is happening, relax and breathe during the walk breaks. · Talk to their coach, and have an active dialogue at all times. · Turn off external distractions so that they could focus! · Organizing life around, before the training session. Especially in time! · Give the horse time. · Work out your own body. · Practice their stress level and their mental capacity and awareness of how to react in different situations. · Train to compete and train on riding the programs a lot before a competition. · Sort by constructive criticism if you feel you start to take criticism personally. · Ride in different environments, both for their own sake and for the horse.